Changes in Spatiotemporal Patterns of 20th Century Spruce Budworm Outbreaks in Eastern Canadian Boreal Forests - Navarro, Lionel; Morin, Hubert; Bergeron, Yves; Girona, Miguel Montoro (Frontiers in Plant Science, 2018)
In scenarios of future climate change, there is a projectedincrease in the occurrence and severity of natural disturbances inboreal forests. Spruce budworm (Choristoneura fumiferana)(SBW) is the main defoliator of conifer trees in the North American boreal forests affecting large areas and causing marked losses of timber supplies. However, the impact and the spatiotemporal patterns of SBW dynamics at the landscape scale over the last century remain poorly known. This is particularly true for northern regions dominated by spruce species. The main goal of this study is to reconstruct SBW outbreaks during the 20th century at the landscape scale and to evaluate changes in the associated spatiotemporal patterns in terms of distribution area, frequency, and severity. We rely on a dendroecological approach from sites within the eastern Canadian boreal forest and draw from a large dataset of almost 4,000 trees across a study area of nearly 800,000 km2. Interpolation and analyses of hotspots determined reductions in tree growth related to insect outbreak periods and identified the spatiotemporal patterns of SBW activity over the last century. The use of an Ordinary Least Squares model including regional temperature and precipitation anomalies allows us to assess the impact of climate variables on growth reductions and to compensate for the lack of non-host trees in northern regions. We identified three insect outbreaks having different spatiotemporal patterns, duration, and severity. The first (1905–1930) affected up to 40% of the studied trees, initially synchronizing from local infestations and then migrating to northern stands. The second outbreak (1935–1965) was the longest and the least severe with only up to 30% of trees affected by SBW activity. The third event (1968–1988) was the shortest, yet it was also the most severe and extensive, affecting nearly up to 50% of trees and 70% of the study area. This most recent event was identified for the first time at the limit of the commercial forest illustrating a northward shift of the SBW distribution area during the 20th century. Overall, this research confirms that insect outbreaks are a complex and dynamic ecological phenomena, which makes the understanding of natural disturbance cycles at multiple scales a major priority especially in the context of future regional climate change.